Ethnobotanical Survey of Natural Galactagogues Prescribed in Traditional Chinese Medicine Pharmacies in Taiwan - Chao, Jung; Ko, Chien-Yu; Lin, Chin-Yu; Tomoji, Maeda; Huang, Chia-Hung; Chiang, Hung-Che; Yang, Jeng-Jer; Huang, Shyh-Shyun; Su, Shan-Yu (Frontiers in Pharmacology, 2021)
Natural medicinal materials have been used to promote breast milk secretion. Here, we investigated the natural medicinal materials prescribed in traditional Chinese medicine (TCM) pharmacies across Taiwan to induce lactation. We collected medicinal materials from 87 TCM pharmacies, identified them in the prescriptions, and analyzed their drug contents. We examined their botanical origins, biological classifications, traditional usage, and modern pharmacological properties. We used the TCM Inheritance Support System to identify core medicinal materials in galactogenous prescriptions. We collected 81 medicinal materials from 90 galactogenous prescriptions. Leguminosae accounted for 12%, whereas Apiaceae accounted for 7% of all materials examined. The primary medicinal plant parts used were roots and seeds. Nineteen frequently used medicinal materials had a relative frequency of citation of greater than or equal to 0.2. According to their efficacy, 58% were warm, 54% were sweet, and 63% were tonifying; 74% of the frequently used medicinal materials have been showed efficacy against breast cancer. The primary core medicinal material was Angelica sinensis (Oliv.) Diels, whereas the secondary core medicinal materials were Tetrapanax papyrifer (Hook.) K. Koch and Hedysarum polybotrys Hand.-Mazz. Most galactogenous prescriptions consisted of multiple materials from Leguminosae and Apiaceae. The mechanisms underlying galactogenous efficacy warrant further investigations.